Exploitation De L’huître Des Mangroves Crassostrea Gasar (Adanson, 1757) Dans Le Lac Nokoué Au Bénin - Agadjihouede, Hyppolite; Akele, David Géraud; Gougbedji, Armel Ulrich Mahounan; Laleye, Philippe Adédjobi (European Scientific Journal, ESJ, 2017)
This manuscript deals with the exploitation of oysters, Crassostrea gasar, specie highly presented in Lake Nokoué, south of Benin Republic. This study aims to characterize this exploitation through the sociodemographic parameters of oyster farmers, the characteristics of different collection sites, the importance and economic characteristics of the exploitation. Socio-demographic and economic information was collected on the basis of a survey of the operators. The physico-chemical data and on the type of substrate used to characterize the sites were collected on the stations Agbato and Atchakpanoukpa. A total of 65 farmers were surveyed. In general, women dominate the people who exploit the oysters (67.7%). Harvesting and trading are two components of the exploitation of oysters. Harvesting is an essentially masculine activity while trading is reserved to women. The stations Agbato, Donoukpa, Jesukô, Togbigba and Atchakpanoukpa near to Cotonou channel are the harvest sites characterized by high salinity (24.057.70 g / L). The oysters’ exploitation in Lake Nokoué is realized at march to september of each year by 60% of populations surveyed. The oysters’ exploitation weekly generates incomes of F CFA 30 150.77 to the collectors, F CFA 29 703.57 to fishmongers and F CFA 28 763.33 to whom lead the two activities. Oysters’ exploitation is intense at Lake Nokoué and constitutes important source of incomes to the operators.